Costs of surgical procedures in Indian hospitals. Issue 6 (11th June 2013) - Chatterjee, Susmita; Laxminarayan, Ramanan
Abstract : Objective: Despite a growing volume of surgical procedures in low-income and middle-income countries, the costs of these procedures are not well understood. We estimated the costs of 12 surgical procedures commonly conducted in five different types of hospitals in India from the provider perspective, using a microcosting method. Design: Cost and utilisation data were collected retrospectively from April 2010 to March 2011 to avoid seasonal variability. Setting: For this study, we chose five hospitals of different types: a 57-bed charitable hospital, a 200-bed private hospital, a 400-bed district hospital, a 655-bed private teaching hospital and a 778-bed tertiary care teaching hospital based on their willingness to cooperate and data accessibility. The hospitals were from four states in India. The private, charitable and tertiary care hospitals serve urban populations, the district hospital serves a semiurban area and the private teaching hospital serves a rural population. Results: Costs of conducting lower section caesarean section ranged from rupees 2469 to 41 087; hysterectomy rupees 4124 to 57 622 and appendectomy rupees 2421 to 3616 (US1=rupees 52). We computed the costs of conducting lap and open cholecystectomy (rupees 27 732 and 44 142, respectively); hernia repair (rupees 13 204); external fixation (rupees 8406); intestinal obstruction (rupees 6406); amputation (rupees 5158); coronary artery bypass graft (rupees 177 141); craniotomy (rupees 75 982) and functional endoscopic sinus surgery (rupees 53 398). Conclusions: Estimated costs are roughly comparable with rates of reimbursement provided by the Rashtriya Swasthya Bima Yojana (RSBY)—India's government-financed health insurance scheme that covers 32.4 million poor families. Results from this type of study can be used to set and revise the reimbursement rates.